Therapeutic Benefits of Red Garlic: A Narrative Review of Laboratory Studies - Michele Antonelli; Davide Donelli (Biology and Life Sciences Forum)
The consumption of garlic (Allium sativum), recognized for its historical medicinal significance, is linked to diverse health benefits. In particular, red garlic stands out for its distinct anthocyanin content, contributing to its unique pink-purple clove color, yet despite extensive research on the pharmacological properties of garlic extracts, there remains limited evidence specifically addressing the therapeutic potential of red garlic. A narrative search was conducted in February 2024 on PubMed and Google Scholar to identify relevant studies examining the pharmacological effects of red garlic extracts. Following the search of selected databases, 789 articles were retrieved and 10 laboratory studies were included in this literature review, exploring the impact of red garlic extracts on laboratory models of lung and digestive tract phlogosis, cancer, microbial proliferation, obesity, and responses to inflammation or oxidative stress. The studies analyzed both aged and fresh red garlic extracts, with a specific emphasis on water extracts. The outcomes highlighted significant antioxidant and anti-inflammatory properties of red garlic extracts, also suggesting potential pro-metabolic effects that could be beneficial in addressing excessive weight and dyslipidemia. Moreover, the results point to the inhibitory effect on cancer cell proliferation by red garlic byproducts and the superior anti-inflammatory profile of the hydroalcoholic extract. Comparative analyses between red and black garlic extracts indicate inconclusive evidence regarding antioxidant activity. The findings also suggest a high level of tolerability for the gut microbiota. This literature review aims to provide valuable insights into the therapeutic potential of red garlic extracts and emphasizes the need for further research to fully elucidate their benefits and mechanisms of action.